Les innovations financières facteurs d’instabilité au cœur des crises financières Référence au cas algérien - ZEGHBID, NASSIM LOTFI; BENTABET, Ali (Journal of Human Sciences, 2017)
Financial innovation has long-term benefits because it facilitates the process of financial development. But there is a dark side in the development of complex financial products that are increasingly becoming more opaque and speculative, a point that was more motivated by the search of higher yields than by the desire to provide investors with hedging instruments. It is according to its effects and consequences that the subject of financial innovation is a present-day subject and worthy of attention. From the debate over the study and after setting a conceptual framework for studying the key role it played in the subprime crisis of 2008 and the crisis of European debt, we will examine the various consequences of these innovations on the Algerian economy.